Methods for the Measurement of Early Events in Toxoplasma gondii Immunity in Mouse Cells - Alvarez, Catalina (2020)
Critical steps in resistance of mice against Toxoplasma gondii occur in the first 2 or 3 h after the pathogen has entered a cell that has been exposed to interferon γ (IFNγ). The newly formed parasitophorous vacuole is attacked by the IFNγ-inducible IRG proteins and disrupted, resulting in death of the parasite and necrotic death of the cell. Here we describe some techniques that we have used to describe and quantify these events in different combinations of the host and the parasite.